The Effect of Acute Continuous Hypoxia on Triglyceride Levels in Constantly Fed Healthy Men - Jean-François Mauger (Frontiers in Physiology, 2019)
IntroductionElevated plasma triglyceride (TG) concentrations are an important contributor to deleterious metabolic alterations. Evidence in animals suggest that acute exposure to an environment with reduced oxygen inhibits plasma TG clearance and causes important rise in plasma TG, especially in the postprandial state. The objective of this study was to characterize the effects of an acute exposure to normobaric hypoxia on prandial TG levels in 2 distinct lipoprotein subtypes in healthy humans: chylomicrons which are secreted by the intestine and carry dietary lipids, and denser TG carriers (mainly VLDL), which are secreted by the liver and carry endogenous lipids. Plasma lipolytic activity was also assessed. It was hypothesized that hypoxia would reduce prandial plasma lipolytic activity and raise prandial TG levels in both lipoprotein subtypes.MethodsUsing a randomized crossover design, 9 healthy young men were studied for 6 h in a constantly fed state while being exposed to either normobaric hypoxia (FiO2 = 0.12) and normoxic conditions on two different days. Prandial glucose, TG, non-esterified fatty acid (NEFA), and post-heparin plasma lipolytic activity were measured during each session.ResultsSix hours of exposure to hypoxia marginally increase prandial glycemia (+5%, p = 0.06) while increasing insulinemia by 40% (p = 0.04). Hypoxia induced a 30% rise in prandial NEFA levels and tended to slightly increased total prandial TG levels by 15% (p = 0.11). No difference was observed in TG concentrations and metabolism of chylomicrons between conditions. However, TG in the VLDL containing fraction decreased significantly overtime under normoxia but not under hypoxia (time × condition interaction, p = 0.02). No difference was observed in post-heparin plasmatic lipolytic activity between conditions.ConclusionAcute hypoxia in healthy men tends to increase prandial VLDL-TG levels. These results lend support to the increased blood lipid levels reported in animals exposed acutely to lower partial pressures of oxygen.